Bar effects on ionized gas properties and dust content in galaxy centers. Issue Volume 10:Issue S309(2014) (9th February 2015) - Zurita, A.; Florido, E.; Pérez, I.; Coelho, P.; Gadotti, D. A.
Abstract: Observations and simulations indicate that bars are important agents to transfer material towards galaxy centers. However, observational studies devoted to investigate the effects of bars in galaxy centers are not yet conclusive. We have used a sample (Coelho & Gadotti2011 ) of nearby face–on galaxies with available spectra (SDSS database) to investigate the footprints of bars in galaxy centers by analysing the central ionized gas properties of barred and unbarred galaxies separately. We find statistically significant differences in the Hβ Balmer extinction, star formation rate per unit area, in the [Sii ]λ6717/[Sii ]λ6731 line ratio, and notably in the N2 parameter (N2 = log([Nii ]λ6583/Hα)). A deeper analysis reflects that these differences are only relevant for the less massive bulges (≲10 10 M⊙ ). These results have important consequences for studies on bulge formation and galaxy evolution.